Pharmacology of alteplase VS tenecteplase in acute ischemic stroke - Riki Nova (Science Midwifery, 2023)
Administration of rtPA thrombolysis intravenously (IV) as the management of acute ischemic stroke currently shows satisfactory results in overcoming ischemic stroke attacks which can reduce morbidity and mortality. This study aims to analyze the comparison of alteplase vs tenecteplase therapy in patients with acute ischemic stroke in terms of the benefits, safety and risks of both drugs. Article searches were conducted through Google Scholar and Research Gate using the keywords Pharmacology Tenecteplase and Alteplase in Acute Ischemic Stroke, then a total of 25 articles that met the inclusion criteria were reviewed. The results showed that tenecteplase had a fibrin specificity 14 times greater than alteplase, a longer half-life, slower plasma clearance, and 80-fold greater resistance to type 1 plasminogen activator inhibitor (PAI-1). Its half-life of about 18 minutes allows rapid administration of a single bolus. The efficacy in acute ischemic stroke was shown to be significantly higher than tenecteplase with significant initial neurologic improvement. Regarding the safety assessment, there was no difference related to all levels of symptomatic intracerebral hemorrhage, both tenecteplase and alteplase.